Labour Productivity Convergence in 52 Industries: A Panel Data Analysis of Some European Countries - Mahmood, Tahir (International Journal of Economics and Financial Issues, 2012)
Beta convergence and the speed of convergence of labour productivity for 52 industries are studied with a panel of data including 13 European countries. We use fixed effect approach to model the heterogeneity across countries. In primary sector and in service sector, the existence of -convergence is found for all industries. In manufacturing sector, convergence is found for all industries except for electronic and computing equipment industries. In general the speed of convergence estimates show slow adjustment. Speed is highest in the capital intensive industries. In primary production the convergence is slowest in agriculture and fastest in fishing industry. In manufacturing sector the convergence is slowest in food, drink and tobacco, and it is fastest in oil refining and nuclear fuel manufacturing industries. By augmenting the productivity models with labour utilization variable speeds up the convergence. Labour utilization is positively related to productivity growth in primary production industries, ICT producing manufacturing industries, and ICT producing services industries. Keywords: Convergence; Speed of convergence; Labour productivity per person; Labour productivity per hour; Labour utilization JEL Classifications: E1; E2; J; O4